Analisis Konseptual Kewirausahaan Sosial dan Inovasi Sosial: Menciptakan dan Mempertahankan Dampak Keberlanjutan - Bintang Permata Putri; Agung Winarno; Wening Patmi Rahayu (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This conceptual research analyzes the relationship between social entrepreneurship and social innovation as an integrated framework for creating and sustaining sustainable impact. Social entrepreneurship is positioned as a strategic mechanism that combines the disciplines of entrepreneurship, value creation, and community empowerment to address complex social and environmental challenges. Meanwhile, social innovation provides new solutions, approaches, and models that drive systemic change and expand community participation in social development. Through a literature-based analysis, this research demonstrates that the synergy between these two concepts enables organizations to design sustainable business models that balance social mission with economic sustainability. The research findings confirm that sustainable social impact is achieved through three interrelated key pillars: system-oriented innovation, hybrid and adaptive business models, and collaborative ecosystems that strengthen institutional capacity and legitimacy. This research provides theoretical contributions by developing a conceptual framework that integrates social value creation, innovation processes, and sustainability mechanisms. Future research is recommended to empirically test this conceptual model through case studies or mixed approaches to assess its applicability in various socio-economic contexts.